PENGARUH LATIHAN DRILL TARGET SHORTPASS DAN POSSESSION GAME TERHADAP KETEPATAN PASSING DALAM PERMAINAN SEPAK BOLA PADA ATLET USIA 10-13 TAHUN DI CLUB SSB DOMPU UNITED - Ruslin; Johan Irmansyah; Muhsan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aims to analyze the effect of drill target shortpass and possession game training on passing accuracy in football games among athletes aged 10-13 years at the SSB Dompu United club in 2023. The research employed a two-group pretest-posttest design with a sample of 22 athletes. The training methods were tested using the passing accuracy test designed by Irianto (1995). Data analysis was conducted using t-tests, with results showing that both training methods had a significant impact on passing accuracy. The possession game training group showed a greater improvement, with a difference of 1.45 compared to the shortpass target drill group. Statistical analysis revealed that drill target shortpass had a significant effect (t = 4.255 > t-table = 2.086, p = 0.000 < 0.05), and possession game also had a significant effect (t = 7.988 > t-table = 2.228, p = 0.000 < 0.05). These findings suggest that both training methods are effective in improving passing accuracy, with possession game showing a greater effect.